SnO deposition via water based ALD employing tin(ii) formamidinate: precursor characterization and process development. Issue 39 (16th September 2022) - Huster, Niklas; Ghiyasi, Ramin; Zanders, David; Rogalla, Detlef; Karppinen, Maarit; Devi, Anjana
Abstract : We report a new water-based thermal ALD process for the deposition of SnO using a liquid formamidine based tin(ii ) precursor. Abstract : Tin monoxide (SnO) is a promising oxide semiconductor which is appealing for a wide range of applications from channel materials in p-type field effect transistors (FET) to electrode materials searched for next-generation batteries. For the controlled growth of SnO films at low temperatures, atomic layer deposition (ALD) is employed in this study, where the choice of the precursor plays a significant role. A comparative thermal evaluation of four different amidinate-based tin(ii ) precursors and the influence of the ligand sphere on their physicochemical properties revealed that bis( N, N ′-diisopropylformamidinato tin(ii ) (1 ) possesses the required volatility, good thermal stability and sufficient reactivity towards water, to be implemented as the ALD precursor. The water-assisted ALD process resulted in crystalline SnO films on Si substrates with a growth per cycle (GPC) of 0.82 Å at temperatures as low as 140 °C. By employing complementary analytical tools, namely, X-ray diffraction (XRD), atomic force microscopy (AFM), X-ray reflectivity (XRR), Rutherford backscattering spectrometry/nuclear reaction analysis (RBS/NRA) and X-ray photoelectron spectroscopy (XPS), the formation of tin monoxide was confirmed. Finally, the optical properties of the as-deposited films were analyzed via UV-Vis spectroscopy, exhibiting a band gap of 2.74 eV, which further confirms the formation of the targeted SnO phase.